Impaired B-cell function in ERCC2 deficiency - Rossmanith, Raphael; Sauerwein, Kai; Geier, Christoph B.; Leiss-Piller, Alexander; Stemberger, Roman F.; Sharapova, Svetlana; Gruber, Robert W.; Bergler, Helmut; Verbsky, James W.; Csomos, Krisztian; Walter, Jolan E.; Wolf, Hermann M. (Frontiers in Immunology, 2024)
Trichothiodystrophy due to ERCC2 deficiency (TTD1) is associated with susceptibility to infections in the majority of patients. The present study shows that B-cell activation is impaired in these patients, thus contributing to clinically relevant antibody deficiency. In the TTD1 patients studied the ERCC2 mutations led to reduced XPD protein expression. Furthermore, mRNA differential expression analysis revealed that highly important factors such as EGR1, EGR2 and EGR3 as well as IGHM transcripts were significantly downregulated in TTD1 patients thus most likely contributing to the antibody deficiency found in TTD1.